Violence against women in Nepal: Role of health care workers - Joshi, SK (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i2.2695 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 89-90